A Study of Essay Translation Under the Guidance of Werner Koller’s Equivalence Theory: Take Texts in the First Volume of Selected Modern Chinese Essays by Zhang Peiji as Examples - TAN, Xiaoyan (International Journal of Social Science Research, 2024)
As an important part of Chinese literature, Chinese essay plays an essential role in spreading Chinese culture. However, compared with other literary translations, studies of essay translations have been far left behind than those of others. Under this background, this thesis, leveraging qualitative analysis and based on Koller’s equivalence theory, will deeply analyze some translated texts from Zhang Peiji’s first set of Selected Modern Chinese Essays, including the following aspects: the translated texts presenting the original content corresponding to denotative and connotative equivalence; re-appearing of the original style to text-normative equivalence; transferring the original forms and aesthetics to formal equivalence and achieving communicative effect to pragmatic equivalence. In so doing, this thesis will further delve into the features of Koller’s equivalence theory, present more perspectives on analyzing essay translations and try to shed some light on the future essay translation. Finally, this thesis concludes that Koller’s equivalence theory is very helpful in guiding the analysis of translated essays and bringing enlightenment to essay translation. The analysis finds that in his translations, Mr. Zhang Peiji not only has faithfully conveyed the original texts’ contents, but also has maintained the original style and in some cases even represented the source text’s aesthetics. Besides, he has also taken target readers into consideration as a way to achieve better communicative effect. What should be noticed is that the functions, frequency and usages among different aspects of equivalence are varied. Therefore, translators are supposed to adopt different translation strategies and techniques in accordance with specific situations so as to achieve better equivalence effect and improve translation quality.